43.1: Invited Paper: AM MiniLED Local Dimming Backlight Achieving high Dynamic Contrast for 8K Displays. (24th February 2021) - Hu, Daobing; Xiao, Juncheng; Xu, Hongyuan; Fei, Jiayang; Qiu, Yongyuan; Liu, Quansheng; Li, Jia; Zhuang, Jiaqing; Liu, Chunming; Zhang, Xin
Abstract : High Dynamic Contrast as an very important element of high‐end TV market for display, has received extensive attention in the past years. Here, we proposed an AM MiniLED local dimming backlight technology for 75‐inch LCD 8K displays, witch consist of 5184 local dimming zones and can realize area dimming. Compared with the traditional LCD dsplays with a contrast ratio of about 5000 : 1, the 75‐inch 8K AM MiniLED LCD displays can achieve a high dynamic constrast ratio of 1, 000, 000 : 1 and over 1000nits brightness. This AM MiniLED backlight technology can individually control the switch of each zone, which can achieve HDR performance and comparable performance with the other technologys (Dual‐cells and OLEDs). By turning off the dark area directly, the dark state can achieve true black. In addition, the AM MiniLED local dimming Backlight technology clearly indicated that the the low energy consumption, low cost and long life time..